Challenges and Benefits of Creative Writing - Edzgveradze, Lela; Kartsivadze, Ana; Gegenava, Monika (International Scientific Conference “EDUCATION, RESEARCH, PRACTICE” Proceedings, 2024)
In this paper, we present an analysis of the creative writing outcomes that were conducted in two different classrooms. During pedagogical practice, students used the same resource to carry out a creative writing activity. The resource was a sand theater performance based on Guram Petriashvili's "Man Who Loves Rain." Pupils watched the performance without sound and created their own version of the text that was based solely on image. Also, it is important that target classes' experience and academic readiness were quite different. Additionally, the activity was conducted at different times. The process of implementation and analysis of the pupils' works showed that: Regardless their readiness and experience, all pupils actively participated in the process and were able to create interesting work that reflected their individual perspective. Their work was diverse, and practically all of them captured the essential pathos of the text: the pain caused by loss of something precious and sublime. The difference between experience and academic readiness was reflected in length of the works, organization of the text, quality of sentence development, structural coherence, and adherence to spelling norms. The period of implementation influenced the content of the works. In the class where the lesson was conducted during a time of public activism, pupils emphasized themes of national independence, loss of freedom, and personal and national values. The student-teacher had to focus on overcoming psychological barriers in the class with pupils who lacked the necessary experience. She used support and encouragement strategies and successfully managed the problem. In conclusion, we would like to emphasize that creative tasks should be an integral part of classroom practice because: Such tasks help pupils with self-expression and foster personal development. They provide valuable insights into pupils' inner worlds, values, concerns, and aspirations. All pupils can perform these tasks if strategies and activities tailored to their needs are applied.